Sociodemographic, Economic, and Gender Determinants of Household Food and Nutrition Security in Central Sulawesi - I Made Tangkas; Abdul Rahim; Ummu Aiman; Aulia Rakhman (Journal of Health and Nutrition Research, 2026)
Food security is a multidimensional problem in a country, with physical and economic access being important factors in determining conditions at the household and individual levels. The purpose of this study was to analyze the determinants of household food security and nutrition based on sociodemographics, socioeconomics and gender. This type of research uses a cross sectional design. The samples in this study were 300 samples from the province of Central Sulawesi, 150 samples from rural areas and 150 samples from urban areas, selected using clustered sampling. Data were analyzed using quantitative data analysis , P-value of less than 0.05 would be considered significant. The prevalence of food insecurity was higher in rural households (31.3%) than in urban households (18.6%). Maternal nutritional knowledge and individual decision-making on food menus were significant predictors of household food security (p<0.05). Stunting was associated with inadequate energy and protein intake in children and limited women’s empowerment in household food allocation. Most households reported coping strategies such as relying on cheaper foods and reducing meal portions. The conclusion of this study is that food insecurity is associated with low maternal nutritional knowledge and individual decision making about food menus. The incidence of stunting in households in Central Sulawesi is associated with low energy and protein adequacy of children and inadequate empowerment of women in the household